2017
DOI: 10.1016/j.atherosclerosis.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D does not predict statin associated muscle symptoms but is associated with transient increases in muscle damage and pain

Abstract: Background and aims Low vitamin D (VITD) may contribute to statin-associated muscle symptoms (SAMS). We examined the influence of baseline and change in VITD in patients with verified SAMS. Methods SAMS was verified in 120 patients with prior statin muscle complaints using 8-week randomized, double-blind crossover trials of simvastatin (SIMVA) 20 mg/d and placebo. 25 (OH)vitamin D was measured at each phase of the trial. Results Forty-three patients (35.8%) experienced muscle pain on SIMVA but not placebo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In fact, both are associated with a range of lifestyle-related features, including low educational attainment, smoking, and physical inactivity [50,51,52]. In this context, it is worth mentioning that exercise-induced tissue damage and lipid peroxidation have been significantly lowered by vitamin D treatment in severely deficient human subjects [53]. Finally, the low serum levels of vitamin D have been associated with high fatigue severity in older subjects [54].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both are associated with a range of lifestyle-related features, including low educational attainment, smoking, and physical inactivity [50,51,52]. In this context, it is worth mentioning that exercise-induced tissue damage and lipid peroxidation have been significantly lowered by vitamin D treatment in severely deficient human subjects [53]. Finally, the low serum levels of vitamin D have been associated with high fatigue severity in older subjects [54].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation may mitigate muscle symptoms [65,66], although this is not a consistent finding [67][68][69]. In our CoQ10 in Statin Myopathy Trial, we found no relationship between vitamin D levels, pre-and post-statin therapy, or clinical vitamin D deficiency and insufficiency, on the development of SAMS [70]. Nonetheless, vitamin D repletion when appropriate is recommended given the overall importance of vitamin D for muscle function.…”
Section: What Are the Most Effective Treatment Strategies For Managinmentioning
confidence: 73%
“…Taylor et al also found that vitamin D deficiency or insufficiency and changes in vitamin D levels during statin therapy did not predict the occurrence of SAMS. 20 As the current study was conducted in India, and many Indian people have insufficient levels of vitamin D, we converted their levels into percentiles, which revealed that the chance of occurrence of SAMS was significantly increased in those with vitamin D levels less than or equal to the 5th, 10th and 25th percentiles. This association was not significant at a percentile cut-off level of 50, which corresponds to vitamin D levels of ≥20.12 ng/mL.…”
Section: Discussionmentioning
confidence: 99%